FreeCall, a System for Emergency-Call-Handling Support - Post, W. M.; Koster, W.; Šrámek, M.; Schreiber, G.; Zocca, V.; de Vries, B. (Methods of Information in Medicine, 1996)
This article describes a system for the optimization of the pre-hospital assessment of emergency, in cases involving thoraco-abdominal complaints and consciousness problems. This assessment is performed by nurses on the basis of a telephone interview at ambulance dispatch centers. The system has a body of biomedical and policy knowledge available to guide the interview and to provide advice.
Keywords: Artificial Intelligence; Decision Support; Differential Diagnosis; Emergency Medicine